Brief report: error pattern in an autistic savant calendar calculator. - Iavarone A; Patruno M; Galeone F; Chieffi S; Carlomagno S (Journal of Autism & Developmental Disorders, 2007)
Special ability in computing the day of the week from given dates was observed in a 18 years old male, L.E., suffering from autism. Neuropsychological testing revealed severe deficits in all cognitive domains and poor explicit knowledge of calendar structure. The subject scored well above the chance level on dates of the past and future decades. Error rate and response latency increased with temporal remoteness of dates. Most of errors were in indicating the weekday before or after that of date stimulus. The performance and error pattern suggest that L.E. used 'encapsulated' computation algorithm(s) for the day of week task.